Efficacy of Saccharomyces cerevisiae NBRC 0203, Lactobacillus plantarum NBRC 3070 and Lactobacillus casei NBRC 3425 as a technological additive (silage additive) for all animal species. (23rd April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The product under assessment is a preparation containing single strains of Saccharomyces cerevisiae, Lactobacillus   plantarum and Lactobacillus   casei to be used as a technological additive to improve the ensiling process. EFSA has been previously requested by the European Commission to evaluate this product. The safety of the additive for consumers, users, the environment and target animals was established at that time. There was, evidence for improved aerobic stability in forage materials with dry matter contents varying between 30% and 70%. Fluorescence in situ hybridisation methods were also introduced and a different culture medium to better characterise the additive but the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) remains unable to identify a minimum specification for the product or a minimum effective dose.